science technology and innovation as a matter within technological education (Revista Electrónica REDINE, 2018)
This article deals with universities to include within a matter that concerned only the steps to create technology because it often projects are launched without really knowing the needs of society, must take into account many points in order to develop technology really good and useful to society as well be What are the needs of society? What do you want to accomplish with this project? In what ways will benefit society? How to publicize the project effectively? ... etc. etc. As can be seen developing technology is not only innovate but also to think ahead and think not only benefit itself but also must think about the benefit of society as this be able to decide if our technology to succeed or quite the contrary.
Keywords: science; technology; innovation; projects; education